Legal Policy on the Use of Weapons by Law Enforcement Officers from the Perspective of Protecting the Right to Freedom of Expression - Nur Sya'ban; Ariawan Gunadi (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This study examines the issue of the use of force by law enforcement officers in managing demonstrations, particularly from the perspective of protecting the right to freedom of expression. Although demonstrations are a constitutional right guaranteed by the 1945 Constitution of the Republic of Indonesia and international human rights instruments, in practice, there have been various violations of human rights principles—such as the disproportionate use of force, arrests without clear justification, and limited access to legal assistance for detained protesters. Law enforcement personnel often face a dilemma between maintaining public order and the risk of being accused of human rights violations, while civilians—including those not directly involved—often suffer the consequences of anarchic demonstrations. This research highlights the urgent need for a human rights-based approach in managing public protests, through enhancing the professionalism and capacity of law enforcement, strengthening dialogue among stakeholders, and improving compensation mechanisms for affected parties. A holistic approach is essential to achieving a balance between safeguarding the right to free expression and maintaining public order in Indonesia.